Regional Inequality and Internal Conflict - Christian Leßmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper studies the influence of interregional inequality within countries on internal conflicts. Regional inequalities are measured by the population-weighted coefficient of variation of regional GDP per capita. As the main innovation, I use a panel data set of country-level regional inequalities, which covers 56 countries (835 subnational regions) between 1980 and 2009. I also consider a broader cross-section data set for the year 2005, which covers 110 countries (1569 subnational regions). Conflict is measured by the incidence of civil war (UCDP/PRIO data) and a risk measure of internal conflict (war, terrorism, and riots) provided by the PRS Group s International Country Risk Guide. Logit estimations are employed as well as OLS fixed effects panel regressions. I find that regional inequalities increase the risk of internal conflict.
Keywords: D63; D74; O15; 330